Development of Madrasah Head Leadership Module to Improve MTsN Teacher Performance in Palembang - Alimin Alimin (Sustainable, 2023)
This study aims to develop a module on the leadership of the head of the Madrasah to improve the performance of a teacher of MTsN di Palembang valid, practical, and effective. The method used in this research is Research and Development using a model of ADDIE. The subject of this research is MTsN 1 Palembang. Analysis techniques in this study use interviews, observation, documentation, and tests. The results of this study are the assessment carried out by material experts, media experts, and workshop instructors collaborating with researchers as expert speakers and media experts. The module is declared practical with the results of the questionnaire responses. Participants obtained a score of 4.55, while the questionnaire respondents from instructor workshops obtained a score of 4.44 and entered the classification as very good, so it is worth using in the leadership of the head of the Madrasah to improve the performance of a teacher of MTsN di Palembang as well as the test results of the workshop conducted at the end of the research, the modules developed are categorized effectively demonstrated by the percentage of mastery learning, the workshop participants are on the classification very well with the results of the average value of the 4 participants (88%) of respondents considered complete (pass) and only 1 participant (12%) have not been completed (no pass). The conclusion is that this module was successfully developed and declared valid, practical, and effective.